Sulfonation of low-density polyethylene and its impact on polymer properties - Kazimi, M.R. (John Wiley and Sons Inc, 2014)
Sulfonation of polymers is of great importance for the packaging industry mainly due to its effect on the alteration of surface functionality of polymer films. In this study we customized liquid phase sulfonation of low-density polyethylene (LDPE) swelling the polymer by using a combination of polar and nonpolar solvents. Swollen polymer was treated with sulfuric acid of varying concentrations with continuous mixing for in-depth sulfonation of the polymer. Presence of cyclohexane and ethanol, as polar and nonpolar reagents, not only kept the batch under isothermal conditions but also homogenously influenced indepth functionalization of LDPE. The durability of the sulfonated polymer was determined by grinding the test samples 30 days after the reaction. Fourier transforminfrared spectroscopy indicated presence of functional group moieties, which is also supported by increase of 5 and 1.35 in density and sulfur contents of the polymer, respectively. Contact angle measurements indicate 30Â° decrease in values of the sulfonated polymer which corresponds with decrease in carbon to hydrogen ratio (from 5.9 to 5.3) and increase in sulfur to carbon ratio (up to 0.0184) resulting from the sulfonation of the polymer. Differential scanning calorimetery results indicate almost linear reduction in the crystallinity of LDPE with an increase in acid concentration used for the sulfonation reaction. Â© 2013 Society of Plastics Engineers.